Corruption and Illegal Trade: The Influence of Election Results on Organized Crime (Kriminalističke teme, 2002)
Bosnia and Herzegovina is heading towards October elections, that will decide about structure of the government for the next four years mandate. Considering that political and security situation still does not attract foreign private capital, it is useful to apply comparative analysis with other states in the region and to become more familiar with possible influences of election results on the parts of organized crime. This essay is concerned with causal relation of political aspects (proces of democratisation, elections) on the security situation (movements and actions of organised criminal organisations).